2019
DOI: 10.1111/jop.12911
|View full text |Cite
|
Sign up to set email alerts
|

A review and guide to drug‐associated oral adverse effects—Dental, salivary and neurosensory reactions. Part 1

Abstract: Numerous adverse drug reactions (ADR) manifest in the oral cavity and orofacial region. Dentists and other health professionals commonly encounter and manage these adverse effects however, due to lack of awareness and training, they are not always recognised as being drug‐induced nor reported to pharmacovigilance agencies. The broad diversity and increasing number of medications for which dental pharmacovigilance is needed can be overwhelming for all health professionals. Thus, the aim of this review and guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“… Addy et al (1985) reported that certain metals (especially iron and tin) can cause tooth discoloration. For example, dark brown to black discoloration was observed in people taking iron supplements, and oral iron salts in liquid form could cause the teeth to appear greenish black ( Teoh et al, 2019 ). Sucroferric oxyhydroxide represents a phosphate binder that effectively controls serum phosphorus amounts in chronic kidney disease cases on dialysis and is mainly supplied as chewable tablets for oral use in a brown color.…”
Section: Discussionmentioning
confidence: 99%
“… Addy et al (1985) reported that certain metals (especially iron and tin) can cause tooth discoloration. For example, dark brown to black discoloration was observed in people taking iron supplements, and oral iron salts in liquid form could cause the teeth to appear greenish black ( Teoh et al, 2019 ). Sucroferric oxyhydroxide represents a phosphate binder that effectively controls serum phosphorus amounts in chronic kidney disease cases on dialysis and is mainly supplied as chewable tablets for oral use in a brown color.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the diagnosis and identification of osteochemonecrosis of jaw due to the ADRs of bisphosphonates through ADR reporting during the postmarketing phase of these drugs have been an important contribution of dentists that influenced the dental and medical management of the patients currently treated with these drugs. 25 During their routine practice, it is the responsibility of dentists to thoroughly check and record the general health and medication history of patients and to update the history at every visit. 6 In a recent study, 60% of dental research assistants stated that they asked about the patient's drug history when interacting with a patient for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…ADRs can also affect the salivary glands, causing hyposalivation (reduced saliva flow), leading to a dry mouth, or they can cause secondary Sjogren's syndrome due to medications such as PD-1 immune checkpoint inhibitors [17]. Conversely, some patients may develop excessive salivation (sialorrhea), resulting in increased saliva or difficulty swallowing due to medications such as antipsychotics, general anesthetics, anticholinesterases, anxiolytics, anticonvulsants, and others [18].…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsic and extrinsic dental pigmentation, which are characterized by tooth discoloration, can be a side effect of certain medications, such as antibiotics, chlorhexidine, and fluoride supplements [16]. Drug-induced bruxism, which refers to the involuntary grinding or clenching of teeth, can be triggered by medications such as anxiolytics, antidepressants, antipsychotics, and other drugs that affect serotonin and noradrenaline reuptake [18]. Lastly, jawbones can also be affected by ADRs due to the onset of osteonecrosis.…”
Section: Introductionmentioning
confidence: 99%